The Portuguese obstetricians’ preconception counselling during COVID19 pandemic - Gonçalves-Henriques,Manuel (2020)
Abstract Overview and Aims: During the COVID19 pandemic, preconception counselling has been a big challenge for health professionals, due to the potential complications of this infection during pregnancy. This study aimed to evaluate the preconception counselling of the Portuguese Obstetricians. Study Design: Cross-sectional study. Population: Portuguese Obstetricians and residents in Obstetrics and Gynaecology. Methods: The Portuguese obstetricians were asked to complete a survey comprising questions regarding their preconception recommendations in general and in specific situations during the pandemic. Their major concerns towards pregnancy during this period and their opinion about vaccination against SARS-CoV2 before pregnancy were also addressed. Results: A total of 325 answers were obtained. More than half of the Portuguese obstetricians and residents would be in favor of plans of pregnancy (53,2%) especially in a young and healthy woman, while some would rather recommend waiting a few months (39,7%). Most of them would also endorse reproductive treatments (51,4% in young patients and 57,5% in patients older than 40 years old). On the other hand, most of them would not encourage planning pregnancy in case of immunosuppression (72,3%), respiratory or cardiac maternal condition (74,2%). In general, the main concerns about pregnancy during the pandemic were the risk of preterm labor, risks related to maternal health and lower availability of medical care services. The vast majority of the respondents were in favor of vaccinating women during the preconception period, both during (93,3%) and after the pandemic (76,6%). Conclusion: The Portuguese obstetricians are aware of some potential complications of COVID19 pandemic during pregnancy, especially those concerning preterm labor and maternal health, but the majority of the respondents would be in favour of pregnancy planning during the pandemic period. If available, vaccination would be highly recommended before pregnancy.